IMPLEMENTASI MEDIA KUIS DALAM MENINGKATKAN PEMAHAMAN NILAI-NILAI AKHLAK SISWA PADA MATA PELAJARAN AKIDAH AKHLAK DI MI MIFTAHUL ULUM PUNTIR PURWOSARI PASURUAN - Lailatul Kudriyah; Ali Mohtarom (STKIP Subang, 2026)
The cultivation of moral values is one of the primary objectives of Islamic education, particularly in Madrasah Ibtidaiyah. However, conventional learning methods often fail to actively engage students, resulting in low motivation and limited understanding of moral concepts. This study aims to describe the implementation of quiz media in Aqidah Akhlak learning, analyze students' understanding of moral values after participating in quiz-based learning activities, and identify students' motivation and participation during the learning process. This research employed a descriptive qualitative approach conducted at MI Miftahul Ulum Puntir Purwosari Pasuruan. Data were collected through classroom observations, in-depth interviews with teachers and students, and documentation. The data were analyzed using data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings indicate that the implementation of quiz media was carried out through three stages: planning, implementation, and evaluation. Quiz media created a more interactive and enjoyable learning atmosphere, encouraged active student participation, and improved students' understanding of moral values such as honesty, responsibility, discipline, and respect. In addition, the use of quiz media increased students' learning motivation and classroom participation. Supporting factors included teacher competence, students' enthusiasm, and adequate learning facilities, while limited instructional time and technical constraints became the primary obstacles. Therefore, quiz media can serve as an effective interactive learning strategy to strengthen students' understanding of moral values in Aqidah Akhlak learning.